Pelaksanaan Ekstensifikasi Saat Pandemi Covid 19 Di Kantor Pelayanan Pajak ABC - wijaya, suparna; Silitonga, Desy Frenstantiasari (Balance Vocation Accounting Journal, 2021)
Tax extensification is the government's effort to increase state revenue by expanding tax objects and subjects. The efforts of the Directorate General of Taxes faced their challenges amid the COVID-19 pandemic. The purpose of this study was to find out the implementation of extensification activities, the impact of extensification on tax revenues, the barriers to extensification, and the extensification amid the COVID-19 pandemic. The research method used was descriptive qualitative. The object of this study is one of the tax service offices (KPP) in the province of North Sumatra. The results showed that the implementation of extensification was performed as stipulated in taxation laws and regulations. However, although extensification has succeeded in increasing the number of registered taxpayers, it is not significant in increasing the amount of tax revenue. Barriers to the implementation of extensification are the difficulties to find taxpayers and the emergence of resistance to tax compliance. The implementation of tax extensification amid the COVID-19 pandemic was carried out by adjusting the situation, such as optimizing the use of letters and reducing the number of visitation